Identification and characterization of RSIY-11, a novel seminal peptide derived from semenogelin-1, which acts as a neutral endopeptidase inhibitor modulating sperm motility - Fritz, Rani (J Assist Reprod Genet, 2019)
PURPOSE: Based on prior reports demonstrating that neutral endopeptidase (NEP) inhibitors increase sperm motility, the goal of our studies was to identify endogenous seminal peptides that inhibit NEP and investigate their potential effect on sperm motility. METHODS: Peptidomic analysis was performed on human seminal fluid, identifying 22 novel peptides. One peptide, named RSIY-11, derived from semenogelin-1, was predicted through sequence analysis to be a substrate and/or potential inhibitor of NEP. Enzymatic analysis was conducted to determine the inhibitory constant (Ki) of RSIY-11 as an inhibitor of NEP. Total and progressive sperm motility was determined at baseline and 30 and 60 min following addition of RSIY-11 to seminal fluid in 59 patients undergoing an infertility workup at an urban medical center. Additionally, the effects of RSIY-11 on sperm motility were evaluated in 15 of the 59 patients that met criteria for asthenospermia. RESULTS: RSIY-11 was shown to act as a competitive inhibitor of NEP with a Ki of 18.4 ± 1.6 μM. Addition of RSIY-11 at concentrations of 0.75 μM, 7.5 μM, and 75 μM significantly increased sperm motility at all time points investigated, with increases of 6.1%, 6.9%, and 9.2% at 60 min, respectively. Additionally, within the subgroup of patients with asthenospermia, RSIY-11 at concentrations of 0.75 μM, 7.5 μM, and 75 μM significantly increased sperm motility at all time points investigated, with increases of 7.6%, 8.8%, and 10.6% at 60 min, respectively. CONCLUSIONS: RSIY-11 is a newly identified semenogelin-1-derived peptide present in seminal fluid. RSIY-11 acts as a potent competitive inhibitor of NEP, which when added to seminal fluid significantly increases sperm motility. RSIY-11 could play a potential role in the treatment for male factor infertility related to asthenospermia and improve intrauterine insemination outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-019-01524-8) contains supplementary material, which is available to authorized users.